2020
DOI: 10.1039/d0sc03955a
|View full text |Cite
|
Sign up to set email alerts
|

Spatial confinement alters the ultrafast photoisomerization dynamics of azobenzenes

Abstract: Ultrafast transient absorption spectroscopy reveals new excited-state dynamics following excitation of trans-azobenzene (t-Az) and several alkyl-substituted t-Az derivatives encapsulated in a water-soluble supramolecular host–guest complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 59 publications
(90 reference statements)
1
39
0
Order By: Relevance
“…The calculated potential energy curves are consistent with the experimental observations. The results presented here support the conclusion that molecules on confinement behave differently. In addition, the dynamics displayed by two anthracene molecules in a confined space discussed here provides insight into photodimerization reactions of organic molecules in restricted spaces offered by crystals, templated structures, biological systems, and host–guest complexes…”
Section: Discussionsupporting
confidence: 77%
“…The calculated potential energy curves are consistent with the experimental observations. The results presented here support the conclusion that molecules on confinement behave differently. In addition, the dynamics displayed by two anthracene molecules in a confined space discussed here provides insight into photodimerization reactions of organic molecules in restricted spaces offered by crystals, templated structures, biological systems, and host–guest complexes…”
Section: Discussionsupporting
confidence: 77%
“…These results can be explained by the spatial confinement effect which plays a pivotal role in photoisomerization of azobenzenes. 35 Our photo-switchable compounds are composed of two bulky paromomycin molecules linked by an azobenzene group and the compounds require a high degree of conformational freedom to switch between the two photo-isomeric forms. However, when the E isomer binds to the aptamer domain of the switch, the compound encounters a sterically hindered environment that confines space and hinders free rotation to convert the E to Z isomer.…”
Section: Resultsmentioning
confidence: 99%
“…159 The classical cis-trans isomerization of azobenzene incorporated into the hydrophobic cavity of another supramolecular complex was observed. 160 The rate of the excited state reaction was again slowed down, and the photochemical yields modified by the confinement.…”
Section: Other Excited State Reactions In Micellesmentioning
confidence: 99%
“…Very recently there have been some time resolved transient absorption studies in strongly confining media by Otolski et al 160,167,168 For a series of encapsulated azobenzene and stilbene derivatives they observed both significant lengthening of excited state lifetimes and the opening up of new isomerization pathways. It was suggested that spatial confinement modifies the topology of the conical intersection with the ground electronic states, thus excited state lifetime and the photoproduct yield.…”
Section: Other Excited State Reactions In Micellesmentioning
confidence: 99%
See 1 more Smart Citation